TAI CHI SEBAGAI MODALITAS REHABILITASI STROKE - Jimmy,* Yudy Goysal,* Andi Kurnia Bintang,* Muhammad Iqbal Basri,* Nilla Mayasari** (NEURONA, 2019)
CHI IS A CHINESE TRADITIONAL MINDBODY EXERCISE AND IS WELL KNOWN FOR ITS SLOW AND GRACEFUL MOVEMENTS TAI CHI HAS BEEN PRACTICED FOR CENTURIES AND HAS BECOME A POPULAR EXERCISE WORLDWIDE IN RECENT YEARS TAI CHI IS BENEFICIAL TO CARDIORESPIRATORY FUNCTION MUSCULAR STRENGTH BALANCE FLEXIBILITY MICROCIRCULATION PSYCHOLOGICAL PROFILE AND QUALITY OF LIFE